2020
DOI: 10.33545/26164485.2020.v4.i4d.279
|View full text |Cite
|
Sign up to set email alerts
|

Homoeopathic management of depression with comorbid eczema: A case report

Abstract: Depression is a common mental disorder that presents with depressed mood, loss of interest or pleasure, decreased energy, feelings of guilt or low self-worth, disturbed sleep or appetite, and poorconcentration. A case of 53 years old female is reported to out patient department of National homoeopathy research institute in mental health, Kottayam on 25/10/19 with symptoms of severe depression with eczema on the right hand. Ignatia was selected after detailed case taking and Repertorization with due consultatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Thus, homoeopathic medicines can be adopted as an effective and safe treatment mode for reducing the burden of illness without reporting the adverse effects during the intervention. Results of many studies [8][9][10][11][12][13][14] support the effectiveness of homoeopathy in treating eczematous disorders, but rigorous clinical trials, especially randomised controlled trials, are needed for further validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, homoeopathic medicines can be adopted as an effective and safe treatment mode for reducing the burden of illness without reporting the adverse effects during the intervention. Results of many studies [8][9][10][11][12][13][14] support the effectiveness of homoeopathy in treating eczematous disorders, but rigorous clinical trials, especially randomised controlled trials, are needed for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…7 Eczema with comorbid depression cases was also successfully treated with homoeopathic medication. [8][9][10][11] However, an individualised approach and administration of oral medication that is palatable to even children without any topical application yield better results in eczema. [12][13][14] Kass et al confirmed the effectiveness and cost-effectiveness of treatment in atopic dermatitis and other chronic disorders with additional enrolment to homoeopathic-integrated care in Germany.…”
Section: Introductionmentioning
confidence: 99%